Association between resting heart rate and cardiovascular risk factors in adolescents - Farah, Breno Quintella; Christofaro, Diego Giulliano Destro [UNESP]; Balagopal, P. Babu; Cavalcante, Bruno Remigio; de Barros, Mauro Virgílio Gomes; Ritti-Dias, Raphael Mendes (Springer Nature, 2015)
This cross-sectional study was performed in 2011 and included 4619 Brazilian adolescents (14–19 years old) to analyze the association between elevated resting heart rate (RHR) and cardiovascular risk factors in boys and girls. RHR and blood pressure were measured using an oscillometric monitor. Overweight was assessed by body mass index and abdominal obesity by waist circumference. Physical activity levels and sedentary behaviors were obtained using a questionnaire. The effect of clustering of cardiovascular risk factors on RHR was analyzed. For boys, abdominal obesity (b = 0.106, p = 0.003), high sedentary behavior (b = 0.099, b < 0.001), physical inactivity (b = 0.049, p = 0.034), and high blood pressure (b = 0.160, p < 0.001) were associated with RHR, whereas for girls, only high blood pressure was associated with RHR (b = 0.259, p < 0.001), after adjustment for age, period of the day, and other cardiovascular risk factors. Boys with five risk factors presented significantly higher (p < 0.05) RHR values (82.5 ± 13.4 beats min−1) than those for boys without any cardiovascular risk factors (68.8 ± 10.4 beats min−1). The girls with five risk factors presented a mean RHR value of 89.8 ± 9.9 beats min−1 that was higher (p < 0.05) than that for girls who had no risk factors (79.6 ± 10.9 beats min−1). Conclusions: Our study demonstrated that while RHR was associated with cardiovascular risk factors in both sexes, the clustering of risk factors amplified the elevation of RHR in a gender-dependent fashion.What is Known:• Resting heart rate is a marker of cardiovascular disease and mortality in adults and associated with risk factor such as higher levels of blood pressure, triglycerides, glucose, and obesity in children and adolescents.What is New:• The data from the current study suggest that the risk factor clustering is associated with elevated resting heart rate in adolescents and that the clustering of risk factors amplifies the elevation of resting heart rate in a gender-dependent fashion.
Keywords: Adolescent health; Cardiovascular disease; Heart rate; Risk factor